ANALISIS PERILAKU KONSUMEN DALAM MEMBELI SEPEDA MOTOR YAMAHA MIO PADA PT. ALFA SCORPII TELUK KUANTAN - Astuti, Nia Widi; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Consumer behavior is very important for a company, to study consumer behavior will greatly assist the company in identifying the market so that market segment would more effective. Study consumer behavior will also be able to know how consumers in the purchase decision process the factors that influene. The purpose of this study was to determine the basis of consumer behavior in the purchase of motorcycles yamaha mio at PT. Alpha Scorpii, Teluk Kuantan.The method used in this research is descriptive quantitative method. The sampling technique used was accidental sampling with a population of 941 people and the number of samples is 90 respondents. The data were obtained through interviews and questionnaires that measured using a Likert scale.The results of this study indicate that the analysis of consumer behavior in buying a motorcycle yamaha mio at PT. Alpha Scorpii shows the criteria agreed.Keywords : analysis, consumer behavior, consumer behavior factors.